Epidemiology, patterns of care and outcomes of traumatic brain injury in deployed military settings: Implications for future military operations. Issue 2 (14th August 2022) - Dengler, Bradley A.; Agimi, Yll; Stout, Katharine; Caudle, Krista L.; Curley, Kenneth C.; Sanjakdar, Sarah; Rone, Malena; Dacanay, Brian; Fruendt, Jonathan C.; Phillips, James B.; Meyer, Ana-Claire L.
Abstract : MTBI represents a significant problem for the Military with an over-triage rate of 68% due to lack of CT scans far forward. Only 50% of patients were able to return to duty after their mTBI. Better non-CT Diagnostic Tools are needed to improve far forward care. Abstract : BACKGROUND: Traumatic brain injury (TBI) is prevalent and highly morbid among Service Members. A better understanding of TBI epidemiology, outcomes, and care patterns in deployed settings could inform potential approaches to improve TBI diagnosis and management. METHODS: A retrospective cohort analysis of Service Members who sustained a TBI in deployed settings between 2001 and 2018 was conducted. Among individuals hospitalized with TBI, we compared the demographic characteristics, mechanism of injury, injury type, and severity between combat and noncombat injuries. We compared diagnostic tests and procedures, evacuation patterns, return to duty rates and days in care between individuals with concussion and those with severe TBI. RESULTS: There were 46, 309 service members with TBI and 9, 412 who were hospitalized; of those hospitalized, 55% (4, 343) had isolated concussion and 9% (796) had severe TBI, of whom 17% (132/796) had multiple injuries. Overall mortality was 2% and ranged from 0.1% for isolated concussion to 18% for severe TBI. The vast majority of TBI were evacuated by rotary wing to role 3 or higher, including those with isolated concussion. As compared with severe TBI, individuals with isolated concussion had fewer diagnostic or surgical procedures performed. Only 6% of service members with severe TBI were able to return to duty as compared with 54% of those with isolated concussion. Traumatic brain injury resulted in 123, 677 lost duty days; individuals with isolated concussion spent a median of 2 days in care and those with severe TBI spent a median of 17 days in care and a median of 6 days in the intensive care unit. CONCLUSION: While most TBI in the deployed setting are mild, TBI is frequently associated with hospitalization and multiple injuries. Overtriage of mild TBI is common. Improved TBI capabilities applicable to forward settings will be critical to the success of future multidomain operations with limitations in air superiority. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III. Abstract :